Acute ethanol disrupts conditioned inhibition in the male rat - Germé, Katuschia; Pfaus, James G (Psychopharmacology, 2024)
RATIONALE: Alcohol can disrupt conditioned sexual inhibition (CSI) established by first-order conditioning in male rats. CSI can also be induced using second-order conditioning, during which male rats are trained to associate a neutral odor with a nonreceptive female. As a result, when given access to two receptive females (one scented and one unscented) during a copulatory preference test, they display CSI toward the scented female. OBJECTIVE: The present study examined the effect of low-to-moderate doses of alcohol on CSI and brain activation following exposure to alcohol and the olfactory cue alone. METHODS: Sexually-naïve Long-Evans rats received alternate conditioning sessions with unscented receptive or scented (almond extract) non-receptive females. Following the conditioning phase, males were injected with saline, alcohol 0.5 g/kg or 1 g/kg, 45 min before a copulatory test with two receptive females, with one bearing the olfactory cue. Fos activation was later assessed, following exposure to alcohol and the olfactory cue alone, in several brain regions involved in the expression and regulation of male sexual behavior. RESULTS: While males in the saline group displayed sexual avoidance towards the scented female, those injected with alcohol before the copulatory test, regardless of the dose, copulated indiscriminately with both females. Subsequent exposure to alcohol and the olfactory cue alone induced different Fos expression between groups in several brain regions. CONCLUSIONS: Low to moderate doses of alcohol disrupt conditioned sexual inhibition in male rats and induce a differential pattern of neural activation, particularly in regions involved in the expression and regulation of sexual behavior.
Keywords: podněty; Sexual Behavior, Animal; Male; Brain; Rats, Long-Evans; Inhibition, Psychological; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; podmiňování (psychologie); sexuální chování zvířat; Cues; krysa rodu Rattus; Conditioning, Psychological; Animals; látky tlumící činnost CNS; ženské pohlaví; zvířata; Ethanol; ethanol; Rats; mozek; Central Nervous System Depressants; protoonkogenní proteiny c-fos; potkani Long-Evans; inhibice (psychologie); Female; Dose-Response Relationship, Drug; Proto-Oncogene Proteins c-fos